Marketable wealth in a poor African country: Using an index of consumer durables to investigate wealth accumulation by households in Ghana - Ronelle Burger; Frikkie Booysen; Servaas van der Berg; Michael von Maltitz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The study uses an asset index of consumer durables to track changes in household wealth in Ghana during the recent period of strong growth. Using the Ghana Living Standards Survey of 1998 that contains both wealth data and consumer durable data, the authors demonstrate that the asset index approximate marketable wealth adequately. Although asset index estimates of wealth cannot match the precision of wealth surveys, this approach can provide useful information on marketable wealth in countries where more appropriate sources are not available. The asset index analysis with the three demographic and health surveys for 1993, 1998 and 2003 suggests that the solid economic growth seen over this period has been accompanied by a strong rise in the average asset index scores. – wealth ; Ghana ; asset index
Keywords: E21; O55; 330; Vermögensverteilung; Index; Afrika